2002
DOI: 10.1007/s00122-002-0923-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of QTLs associated with greenbug resistance and tolerance in Sorghum bicolor

Abstract: Ninety three recombinant inbreds of Sorghum bicolor (L. Moench) were derived from a cross between two sorghum lines GBIK and Redlan. This population was used to identify quantitative trait loci (QTLs) for resistance and tolerance to greenbug ( Schizaphids graminum Rondani) Biotypes I and K. One hundred and thirteen loci (38 SSRs and 75 RAPDs) were mapped in 12 linkage groups covering 1,530 cM. In general, nine QTLs were detected affecting both resistance and tolerance to greenbug (GB) Biotypes I and K. The phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…Recently, SSR markers have been developed for sorghum, which are quite useful for cultivar identification, and resistance to biotic and abiotic stresses (Dean et al, 1999;Dje et al, 2000;Grenier et al, 2000;Smith et al, 2000). The SSR markers linked to QTLs associated with shoot fly-resistance traits such as leaf glossiness, trichome density, and deadhearts Agrama et al (2002) identified 9 QTLs associated with resistance and/ or tolerance to green bug, Schizaphis graminum (Rondani) biotypes I and K. Both resistance and tolerance to green bug biotypes I and K are controlled by QTL linked to four SSR (Sb5-214, Sb1-10, SbAGB03, and SbAGA01) and one RAPD (OPB12-795) markers, and these markers appeared to be linked to biotype non-specific resistance and tolerance genes. This is the first report on the molecular characterization of shoot fly-resistant and -susceptible hybrids and their parents using the SSR loci employed for mapping QTL for shoot fly resistance in sorghum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, SSR markers have been developed for sorghum, which are quite useful for cultivar identification, and resistance to biotic and abiotic stresses (Dean et al, 1999;Dje et al, 2000;Grenier et al, 2000;Smith et al, 2000). The SSR markers linked to QTLs associated with shoot fly-resistance traits such as leaf glossiness, trichome density, and deadhearts Agrama et al (2002) identified 9 QTLs associated with resistance and/ or tolerance to green bug, Schizaphis graminum (Rondani) biotypes I and K. Both resistance and tolerance to green bug biotypes I and K are controlled by QTL linked to four SSR (Sb5-214, Sb1-10, SbAGB03, and SbAGA01) and one RAPD (OPB12-795) markers, and these markers appeared to be linked to biotype non-specific resistance and tolerance genes. This is the first report on the molecular characterization of shoot fly-resistant and -susceptible hybrids and their parents using the SSR loci employed for mapping QTL for shoot fly resistance in sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…Classification of germplasm accessions solely based on discrete morphological characters may not provide an accurate indication of their genetic divergence (Menkir et al, 1997), and phenotypic selection based on traits that are conditioned by additive allelic effects can produce dramatic and economically important changes in breeding populations. Molecular markers have been used for rapid, detailed, and directed genetic manipulation of crop plants, and to identify and characterize quantitative trait loci (QTLs) associated with plant height and days to maturity (Pereira & Lee, 1995), plant domestication (Paterson et al, 1995), resistance to diseases (Gowda et al, 1995) and insects (Agrama et al, 2002), and tolerance to drought (Tuinstra et al, 1998). The SSR markers are co-dominant, flanking, uniformly distributed, and highly polymorphic in plants, and even among the closely related accessions (Morgante & Olivieri, 1993;Wang et al, 1994;Rongwen et al, 1995;Yang et al, 1995;Brown et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, LG A seems to be important in harboring genes for insect resistance in sorghum. Only one QTL linked to Sb1_10 was common with those reported by Agrama et al (2002). The differences in QTLs identi脼ed may be because of more advanced mapping methods applied in our current study and because of the far larger number of SSRs we used.…”
Section: Discussionmentioning
confidence: 45%
“…In the current study, we expanded on work begun by Agrama et al (2002) and evaluated a set of 173 SSR markers from Bhattramakki et al (2000), 38 SSR markers from Kong et al (2000), 17 SSR markers from Brown et al (1996), 13 SSR markers from Taramino et al (1997), and 60 SSR markers from Schloss et al (2002). These 301 markers (representing 75% of currently available public domain sorghum SSR markers) were screened for polymorphism to build a genetic linkage map and identify QTLs associated with tolerance to greenbug biotypes I and K feeding damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation